Service quality meets patient loyalty: the strategic role of standardization in healthcare management (Economics and region, 2025)
The article examines various tools and strategies for strengthening trust and satisfaction in healthcare through the implementation of certified quality standards. It identifies two primary directions: personalization and empathy in patient care, as well as standardization and the use of formalized evaluation instruments. Using Scopus and VOSviewer analyses, the study highlights the multidimensional impact of quality standards on patient perception of service quality, staff motivation, transparency, and overall institutional trust. Empirical survey results confirmed that certification significantly enhances patient trust, satisfaction, and long-term loyalty. Additionally, the article reviews leading international standards, outlines common barriers and challenges to their implementation, and presents global case studies emphasizing patient-centered approaches, effective communication, and digital tools as essential elements for comprehensive and sustainable loyalty management in healthcare organizations.
Keywords: healthcare standardization; service quality; patient loyalty; healthcare management; health service accreditation; customer satisfaction; ISO standards in healthcare; patient experience; healthcare quality management; patient-centeredness; communication; digital tools